The secret of the great Houdini - Burleigh, Robert; Gore, Leonid (New York : Atheneum Books for Young Readers, 2002)
As Sam and Uncle Ezra watch, the Great Houdini escapes from a trunk at the bottom of the river. Includes factual information about Houdini and his career as a magician and escape artist.
Keywords: Houdini, Harry, -- 1874-1926 -- Juvenile fiction; Houdini, Harry, -- 1874-1926 -- Fiction; Escape artists -- Fiction; Magicians -- Fiction